“Diseño y Simulación de una Red de Comunicación en Vagones de Ferrocarriles a Través de la Utilización de los Estándares IEC 61375 para la Ruta Tren del Hielo I (Riobamba – Urbina – La Moya – Riobamba)” - Maigualema Quimbita, Denis Andrés (2020)
The need for communication services in mobile environments has motivated the development of new technologies in the railway sector; this is how the design and simulation of a communication network for railway wagons in Ecuador on the “Tren del Hielo I” route, this network was designed based on current railway communication standards and protocols, the network is based on the capacity of passengers that are transported on this route, also considering the meteorological conditions that they must endure as well as the rustic environment in which the equipment must operate without drawbacks. In this sense, the network maintains a hierarchical topology where the inter-wagon network was made up of equipment with greater capacities because they direct traffic from wagon to wagon. In contrast, the intra-wagon equipment was used to create its internal network, where in addition to allowing connection with end-user devices, it was used to carry out control and alert tasks. On the other hand, for the train to infrastructure communication, wireless communication technology was chosen which satisfies the calculated bandwidth requirement, while being able to maintain the reception level within the acceptable values that guarantee connectivity and data transmission throughout the route, since a frequency band with less susceptibility to climatic conditions in this area was used.